Synergistic Hydrolysis of Arrowroot (Marantha arundinaceae L.) Starch by ï¡-Amylase, Glucoamylase, and Pullulanase for Glucose Syrup Production - Yunianta, Yunianta; Sulistyo, Tri; Apriliastuti, Apriliastuti; Estiasih, Teti; Wulan, Siti Narsito (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
The purified ï¡-amylase, glucoamylase and pullulanase were used for hydrolysis of arrowroot starch (Marantha arundinaceae L.) a local tuber from Indonesia. This arrowroot starch is a potential source for glucose syrup production. The amylolytic activities of Î±-amylase, glucoamylase (from Aspergillus niger) and pullulanase (from Bacillus licheneformis) were 90 KNU/g, 260 GAU/g and 390 ASPU/g, respectively. These enzymes were used to study their synergistic effects on the hydrolysis of arrowroot starch to glucose syrup. We have studied the effect of Î±-amylase concentration (0.025%, 0.045%, and 0.065% (w/w)) and incubation time (1 hour, 1,5 hours, and 2 hours) during liquefaction process that was combined with 24 hours of saccharification process using 0.08% (w/w) dextrozyme (mixture of glucoamylase and pullulanase) in the glucose Â syrup production. Â This experiment showed that 1.5 hours of liquefaction process using 0.045% (w/w) of ï¡-amylase produced 24.64% of reducing sugar and 91.80 of dextrose equivalent. Â The second experiment was focused on the determination of saccharification process, where 1 hour liquefaction process using 0.045% (w/w) of ï¡-amylase was combined with saccharification process using dextrozyme. In the saccharification process, Â a various dextrozyme concentrations (0.04, 0.06, and 0.08 % (w/w)) and incubation times (24 hours, 48 hours, 72 hours) were studied in relation to glucose syrup production. Â It was showed that 0.08% (w/w) of dextrozyme and 24 hours of incubation time gave the best result on glucose syrup with 24.88% of reducing sugar and 92.14 of dextrose equivalent.Keywords: arrowroot, ï¡-amylase, dextrozyme, liquefaction, saccharification, glucose syrup